1998
DOI: 10.1007/978-94-015-9056-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Monitoring and Network Design

Abstract: Abstract. In recent years, shortcomings of both the available data on water quality and the existing networks have led designers to focus more critically on the design procedures used. Within this respect, this chapter addresses the prevailing problems associated with water quality monitoring networks and discusses current attempts towards improvement of existing networks. IntroductionIn recent years, problems observed in available water quality data and shortcomings of current monitoring networks have led des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 43 publications
0
39
0
2
Order By: Relevance
“…Economical and water resources data groups (see Table I frequency), determine whether these give enough, redundant or not enough information (adequate, redundant or shortage of information) about the spatial salinity. The main criteria have been used in such studies are transinformation or joint entropy (e.g., Harmancioglu et al, 1999;Mogheir and Singh, 2002;Mogheir et al, 2003a). The assessment stage can indicate whether or not the existing monitoring networks provide adequate information.…”
Section: Quantification Of the Information Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Economical and water resources data groups (see Table I frequency), determine whether these give enough, redundant or not enough information (adequate, redundant or shortage of information) about the spatial salinity. The main criteria have been used in such studies are transinformation or joint entropy (e.g., Harmancioglu et al, 1999;Mogheir and Singh, 2002;Mogheir et al, 2003a). The assessment stage can indicate whether or not the existing monitoring networks provide adequate information.…”
Section: Quantification Of the Information Needsmentioning
confidence: 99%
“…The framework for evaluating the collected data according to the information needs, which are specified according to the objective and tasks, is outlined. Evaluation of these data is based on the entropy theory which measures the information content and the mutual information in a time series of data (e.g., Husain, 1989;Harmancioglu and Alpaslan, 1992;Yang and Burn, 1994). This framework is applied to the data collected from the: (1) groundwater quality monitoring network (Chloride) and (2) groundwater level monitoring network, in the Gaza Strip.…”
Section: Introductionmentioning
confidence: 99%
“…Sanders et al [1], Ward et al [2], Harmancioglu et al [3] and Strobl and Robillard [4] produced an overview of the current network design procedures and developed basic guidelines to be followed in both the design and the redesign of water quality monitoring networks. Their studies treat the network design problem in a comprehensive and systematic framework, starting with objectives of monitoring and elaborating on various technical design features, e.g., selection of sampling sites, sampling frequencies, variables to be monitored, and sampling duration.…”
Section: Introductionmentioning
confidence: 99%
“…It is a highly complicated issue since there are several variables to choose from in representing surface water quality (e.g. [1]). Several methods are available.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies have shown that information transfer between water quality variables is pretty poor (e.g. [1]). …”
Section: Introductionmentioning
confidence: 99%